MODEL SISTEM PENGAWASAN PASAR BERLANDASKAN EKONOMI SYARIAH - Novi Indriyani Sitepu (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2018)
The market is spearheading the economic transactions. The importance of the market is shown also at the time of Muhammad.Prophet Muhammad pbuh. acts as muhtasib and founder of the market that can beat the market Jew at that time. This is the main attraction in this paper. Therefore, extracting the values of the Islamic economic filosophy through the market at the time of Muhammad. is expected to be a model for today's market.